Sortie nature, protocole et hybridité cognitive. Note sur les sciences participatives - Florian Charvolin (VertigO)
The open air experience, away from the confinement of academic disciplines, produces a cognitive hybridity all the more evident in processes of dialogue between scientists and amateurs. The contemporary development of citizen sciences requires an investigation of their manifestation in the wild, and reverses the priority given to the closed space of laboratory to describe science, to the profit of outings and observing protocols in nature. The paper considers this phenomenon of citizen sciences, and proposes a reading of its performances in terms of knowledge acquisition, sociability and other forms of accomplishments.